Increasing understanding to prospective Umrah pilgrims in the Umrah ritual guidance program at PT Arudam 99 Probolinggo Branch - Ridho, Zainur; Assayuthy, Muhammad Jalaluddin (KHIDMAH : Jurnal Pengabdian Masyarakat, 2025)
The purpose of this service is to increase the understanding of prospective pilgrims in the umrah manasik guidance program at PT Arudam 99 Probolinggo Branch, this manasik guidance shows a high commitment to providing an effective and comprehensive learning experience for prospective umrah pilgrims. Methods of implementing activities, such as personal approach, lectures with PowerPoint, interviews, and practice. Results The manasik guidance activity was carried out for three months with six meetings, designed to provide in-depth understanding to prospective pilgrims. In addition, the provision of a WhatsApp group as a forum for post-guidance communication serves to strengthen understanding and build community among prospective pilgrims. The results of the service show that this program is effective in improving the understanding of prospective pilgrims, as well as recommending the development of more innovative learning methods and periodic evaluations for continuous improvement.